Variation of Alfalfa Mosaic Virus (AMV) symptoms in lucerne germplasm - Pecetti L.; Romani M.; Piano E. (Quality in lucerne and medics for animal production, 2001)
14 genotypes within the Medicago sativa complex were morphologically diversified and categorised into four models. Significant differences were found among models and genotypes; the two most erect and vigorous models had higher percentage of plants with symptoms. Genotypes ranged between 1.4 and 97.6 per cent of plants with symptoms. Such a variation appeared to be related with differences in flower colour and, hence, taxonomic origin of the germplasm: the mean frequency of plants with symptoms in purple-flowered genotypes (typically of subsp. sativa) was 70.7 versus 24.6 per cent in genotypes with other flower colours. The two genotypes with the highest percentage and the two with the lowest were again evaluated in the next year and confirmed the sharp differences in symptoms already observed. In addition, a strong relationship was evidenced between the presence of plants with symptoms in a plot and aphid infestation in the same plot.
14. Réunion Eucarpia du Groupe Medicago spp., 2001/09/12-15, Zaragoza and Lleida (Spain)